2021
DOI: 10.1002/jgh3.12544
|View full text |Cite
|
Sign up to set email alerts
|

New endoscopic method for gastric hypersensitivity testing: Pilot study

Abstract: Iwakiri contributed to data acquisition and analysis. All authors read and approved the final version of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 25 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…Consistent with our previous findings [ 8 ], we demonstrated that the initial symptoms occurred with a lower gastric pressure and a smaller CO 2 injection volume in the drug-resistant FD patients than in non-FD patients. Similarly, bothersome symptoms occurred with a lower gastric pressure and a smaller CO 2 injection volume in the drug-resistant FD patients.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with our previous findings [ 8 ], we demonstrated that the initial symptoms occurred with a lower gastric pressure and a smaller CO 2 injection volume in the drug-resistant FD patients than in non-FD patients. Similarly, bothersome symptoms occurred with a lower gastric pressure and a smaller CO 2 injection volume in the drug-resistant FD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Drug-resistant FD is defined as the presence of at least 1 symptom of dyspepsia other than “belching” on the revised F scale [ 9 ] with a score of 4 points (frequency of symptoms: always) or at least 1 symptom of dyspepsia other than “belching” with a score >3 points (frequency of symptoms: often) and a total dyspepsia symptom score >8 points [ 8 ]. Non-FD is defined as a dyspepsia score ≤1 (frequency of symptoms: occasionally) and a total dyspepsia symptom score, excluding “belching”, ≤3 points [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations